Aspectos técnico-vocais e interpretativos do Bel Canto do Século XIX presentes nas Sei Ariette, Op. 95, de Mauro Giuliani - Daiana de Oliveira Melo Roussin (2015)
This study aimed to investigate the presence of technical-vocal aspects of the Italian singing school better known as Bel Canto, in the chamber music repertoire for voice and guitar (or piano) by the Italian composer Mauro Giuliani (1781 1829). In this way, it was first approached historical aspects of this singing school, treating especially the insertion of the female voice in musical performances throughout the XVII, XVIII and XIX centuries, and then selected five technical-vocal aspects belonging to Bel Canto in order to conceptualize and exemplify them in pieces of the operatic repertoire of the nineteenth century. In order to highlight the link between Giuliani and the nineteenth-century vocal practice, there was an inclusion of some aspects of this composers life and work, stressing through biographical, historiographical, and compositional data, his relationship with Gioacchino Rossini, which may justify the dramatic and scenic character of his works. Finally, the study included two types of analysis of the piece Sei Ariette, Op. 95: a traditional and formal analysis detecting, among other things, the five technical and vocal aspects of Bel Canto previously studied; and an analysis of the poem-song, where it was possible to develop a plot to establish unity among all ariettas that make up the work. It was intended, in the light of such analyzes, to incorporate these elements in my performance and elucidate them in the interpretation of the nineteenth century belcantist repertoire.